Monthly records of non-sea-salt sulfur from the Summit2015 ice core in Greenland between 1530 and 1710 CE and inferred background and volcanic contributions - Michael Sigl; Joseph R McConnell; Nathan J Chellman; Imogen Gabriel (PANGAEA, 2025)
We report monthly non-sea-salt sulfur concentrations from the Summit2015 ice core (Greenland) analyzed using inductively coupled plasma mass spectrometry (ICPMS) and mass concentration records of insoluble particles (size range 5-10um) using an inline Abakus® laser particle counter at the Desert Research Institute. Details about the analytical procedures are provided in the references. From the monthly resolved non-sea-salt sulfur concentration record we infer a mean annual cycle of background sulfur concentrations using the median across the respective months in a volcanically quiescent time (1530-1580 CE) while omitting months influenced by smaller volcanic eruptions. We then subtract this mean background cycle from the total sulfur concentrations to derive volcanic sulfate concentrations (ng g-1) and volcanic sulfate depositions rates (kg km-2 month-1) at nominal monthly resolution. These records are used alongside ice-core crypto-tephra to characterize volcanic eruption sources and to disentangle individual volcanic sulfur depositions on the polar ice sheets arising from temporal clusters of volcanic eruptions such as in the 1590s, 1600s, 1640s, 1660s and 1690s CE.
In: Sigl, M et al. (2025): High time resolution records of sulfur and insoluble particle concentrations from five ice cores from Greenland and one from Antarctica between 1530 and 1710 CE and inferred volcanic contributions [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.974177